Exploring Learning Desire: Students' Intrinsic Motivation in English Language Mastery - Matatula, Marles Yohannis; Tupalessy, Pricilia (Huele: Journal of Applied Linguistics, Literature and Culture, 2024)
This study aimed to explore students' intrinsic motivation in learning English and identify the key factors that contribute to their motivation in the English Education Study Program at Pattimura University. The subject of the research was the 6th-semester students in the English Education Study Program at Pattimura University, academic year 2022/2023. The method of this study was descriptive quantitative. Data were collected using a questionnaire. The result showed that students’ intrinsic motivation for learning English was at a good level based on the responses. Motivation to learn English stems from various factors, such as fun in Learning English, Real-World Application, Increased Confidence, Language and Cultural Exploration, Passion to Complete Challenges, Relationship to Personal Growth, and Practical Implications. This research underscores the importance of creating a learning environment that is fun, practically relevant, and rich in cultural aspects to support students' intrinsic motivation. For future researchers, it is recommended to conduct a study on the Influence of Different Learning Environments. Further research could explore how different learning environments (e.g. online, face-to-face, or hybrid learning) affect students' intrinsic motivation in learning English, as well as how each approach can be optimized to support students' motivation and engagement.